MiR224-5p Inhibitor Restrains Neuronal Apoptosis by Targeting NR4A1 in the Oxygen-Glucose Deprivation (OGD) Model - Liu, Ling-Ling; Qiao, Shan; Wang, Mei-Ling; Wu, Huai-Kuan; Su, Yong-Xin; Wang, Ke-Mo; Liu, Xue-Wu (Frontiers in Neuroscience, 2020)
This study was designed to investigate the molecular mechanism of stroke and to explore the effect of miR-224-5p in hypoxic cortical neurons. Firstly, we established a middle cerebral artery occlusion (MCAO) model with Sprague–Dawley rats. Triphenyltetrazolium chloride (TTC) staining showed the brain infarction of an MCAO rat. Longa scores of rats were significantly increased in 12th, 24th, and 48th hours after MCAO. Then, we found that miR-224-5p was increased after MCAO in rats by qRT-PCR. In order to investigate the effect of miR-224-5p in hypoxic neurons, we established an oxygen-glucose deprivation (OGD) model with cortical neurons. MiR-224-5p was also upregulated in neurons after OGD by qRT-PCR. After transfection of the miR-224-5p inhibitor, the number of neurons in the anti-miR-224-5p group significantly increased (P < 0.01) in comparison to the anti-NC group. Furthermore, Tuj1+ (neuronal marker) staining and TUNEL assay (to detect apoptotic cells) were performed in neurons. The survival of neurons in the anti-miR-224-5p group was significantly improved (P < 0.01), while the apoptosis of neurons in the anti-miR-224-5p group was significantly decreased (P < 0.01), when compared with that of the anti-NC group. In addition, we predicted that potential target genes of miR-224-5p were nuclear receptor subfamily 4 group A member 1 (NR4A1), interleukin 1 receptor antagonist (IL1RN), and ring finger protein 38 (RNF38) with bioinformatics databases, such as TargetScan, miRDB, miRmap, and miRanda. The result of qRT-PCR confirmed that NR4A1 was significantly decreased after hypoxic injury (P < 0.01). Meanwhile, luciferase reporter’s assay indicated that NR4A1 was the direct target of miR-224-5p. Compared with the anti-miR-224-5p + siNC group, the number of cortical neurons and the length of the neuron axon in the anti-miR-224-5p + si-NR4A1 group were significantly decreased (P < 0.01), and the number of neuronal apoptosis in the anti-miR-224-5p + si-NR4A1 group was increased (P < 0.01). In conclusion, miR-224-5p played a crucial role in hypoxic neuron injury through NR4A1, which might be an important regulatory mechanism in OGD injury of neurons.